Visualizing the document pre-processing effects in text mining process - Eler, Danilo Medeiros [UNESP]; Pola, Ives Renê Venturini [UNESP]; Garcia, Rogério Eduardo [UNESP]; Teixeira, Jaqueline Batista Martins [UNESP] (Springer Nature, 2018)
Text mining is an important step to categorize textual data by using data mining techniques. As most obtained textual data is unstructured, it needs to be processed before applying mining algorithms – that process is known as pre-processing step in overall text mining process. Pre-processing step has important impact on mining. This paper aims at providing detailed analysis of the document pre-processing when employing multidimensional projection techniques to generate graphical representations of vector space models, which are computed from eight combinations of three steps: stemming, term weighting and term elimination based on low frequency cut. Experiments were made to show that the visual approach is useful to perceive the processing effects on document similarities and group formation (i.e., cohesion and separation). Additionally, quality measures were computed from graphical representations and compared with classification rates of a k-Nearest Neighbor and Naive Bayes classifiers, where the results highlights the importance of the pre-processing step in text mining.
Keywords: Document pre-processing; Document similarity; Multidimensional projection; Text mining; Visualization